Simplified Clinical Prediction Scores to Target Viral Load Testing in Adults with Suspected First Line Treatment Failure in Phnom Penh, Cambodia - van Griensven, Johan (Public Library of Science, 2014)
BACKGROUND: For settings with limited laboratory capacity, 2013 World Health Organization (WHO) guidelines recommend targeted HIV-1 viral load (VL) testing to identify virological failure. We previously developed and validated a clinical prediction score (CPS) for targeted VL testing, relying on clinical, adherence and laboratory data. While outperforming the WHO failure criteria, it required substantial calculation and review of all previous laboratory tests. In response, we developed four simplified, less error-prone and broadly applicable CPS versions that can be done ‘on the spot’. METHODOLOGY/PRINCIPAL: Findings From May 2010 to June 2011, we validated the original CPS in a non-governmental hospital in Phnom Penh, Cambodia applying the CPS to adults on first-line treatment >1 year. Virological failure was defined as a single VL >1000 copies/ml. The four CPSs included CPS1 with ‘current CD4 count’ instead of %-decline-from-peak CD4; CPS2 with hemoglobin measurements removed; CPS3 having ‘decrease in CD4 count below baseline value’ removed; CPS4 was purely clinical. Score development relied on the Spiegelhalter/Knill-Jones method. Variables independently associated with virological failure with a likelihood ratio ≥1.5 or ≤0.67 were retained. CPS performance was evaluated based on the area-under-the-ROC-curve (AUROC) and 95% confidence intervals (CI). The CPSs were validated in an independent dataset. A total of 1490 individuals (56.6% female, median age: 38 years (interquartile range (IQR 33–44)); median baseline CD4 count: 94 cells/µL (IQR 28–205), median time on antiretroviral therapy 3.6 years (IQR 2.1–5.1)), were included. Forty-five 45 (3.0%) individuals had virological failure. CPS1 yielded an AUROC of 0.69 (95% CI: 0.62–0.75) in validation, CPS2 an AUROC of 0.68 (95% CI: 0.62–0.74), and CPS3, an AUROC of 0.67 (95% CI: 0.61–0.73). The purely clinical CPS4 performed poorly (AUROC-0.59; 95% CI: 0.53–0.65). CONCLUSIONS: Simplified CPSs retained acceptable accuracy as long as current CD4 count testing was included. Ease of field application and field accuracy remains to be defined.